DEVELOPMENT OF INDONESIAN COCOA BEAN EXPORTS TO MALAYSIA - Rizqiana Dewi; Mubarokah; Ida Syamsu Roidah (RADJA PUBLIKA, 2024)
Cocoa is one of the commodities that has the largest contribution to the Indonesian economy. Indonesia is one of the largest cocoa producers in the world, most of its production is exported in the form of cocoa beans (HS: 180100). Malaysia is the main export destination for Indonesian cocoa beans. However, exports of Indonesian cocoa beans to Malaysia have decreased due to the decline in Indonesian cocoa production from 2008 to 2022. The aim of this research is to analyze the development of Indonesian cocoa bean exports to Malaysia using trend analysis and identifying factors that influence demand for cocoa bean exports. Indonesia to Malaysia using VECM (Vector Error Correction Models) analysis with the help of Eviews 12 software. The results of this research show that the volume of Indonesian cocoa bean exports to Malaysia has decreased. The factors that significantly positively influence demand for Indonesian cocoa bean exports to Malaysia are the exchange rate, while those that have a significantly negative influence are international cocoa bean prices and inflation.